Exploration of Environmental Care Attitudes in Students Ar-Rohmah Islamic Boarding School Malang Based on the New Ecological Paradigm Instrument - Hidayati, Dewi Arif; Husamah, H.; Fatmawati, Diani; Miharja, Fuad Jaya; Fauzi, Ahmad (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
This study aimed to determine the attitude of concern for the environment among the students at Pondok Pesantren Ar-Rohmah Malang. This research was an ex post facto research where the researcher reveals and describes the facts about the environmental care attitude of the students at Ar-Rohmah Islamic Boarding School Malang. The population in this study were all students of Ar-Rohmah Senior High School Malang. The sample in this study were students of class 10, 11, and 12 SMA Senior High School Ar-Rohmah Malang who were randomly selected with the number of students in each class as many as 35 students and total as many as 210 students. The results showed that in general, the students of Ar-Rohmah Senior High School Malang tend environmental care / pro-environmental attitudes rather than social paradigm attitudes. Class differences indicate a difference in the percentage of caring attitudes towards the environment. If we look at each item, based on the percentage of responses to the NEP instrument, the students of AR-Rohmah Senior High School Malang is not understood holistically on several materials such as the balance of ecosystems, the right of natural resources not to be exploited continuously, and the obligation of humans to protect the environment and cultivate it wisely.